Landscapes of possibility. When autobiography becomes autoethnography - Helen Bohme (Murmurations, 2022)
With many years of experience as a family therapist I became a researcher and embarked upon a Professional Doctorate in Systemic Practice. I had wanted to illuminate the art, craft, and the aesthetics therapy where therapist expertise is creating the space for and architecting a dialogical process. Traditional research methods were too limiting for this project so I created my own bespoke methodology.